Changes in expression of cartilaginous genes during chondrogenesis of Wharton's jelly mesenchymal stem cells on three-dimensional biodegradable poly(L-lactide-co-glycolide) scaffolds. Issue 1 (December 2016) - Paduszyński, Piotr; Aleksander-Konert, Ewelina; Zajdel, Alicja; Wilczok, Adam; Jelonek, Katarzyna; Witek, Andrzej; Dzierżewicz, Zofia
Abstract Background In cartilage tissue regeneration, it is important to develop biodegradable scaffolds that provide a structural and logistic template for three-dimensional cultures of chondrocytes. In this study, we evaluated changes in expression of cartilaginous genes during in vitro chondrogenic differentiation of WJ-MSCs on PLGA scaffolds. Methods The biocompatibility of the PLGA material was investigated using WJ-MSCs by direct and indirect contact methods according to the ISO 10993–5 standard. PLGA scaffolds were fabricated by the solvent casting/salt-leaching technique. We analyzed expression of chondrogenic genes of WJ-MSCs after a 21-day culture. Results The results showed the biocompatibility of PLGA and confirmed the usefulness of PLGA as material for fabrication of 3D scaffolds that can be applied for WJ-MSC culture. The in vitro penetration and colonization of the scaffolds by WJ-MSCs were assessed by confocal microscopy. The increase in cell number demonstrated that scaffolds made of PLGA copolymers enabled WJ-MSC proliferation. The obtained data showed that as a result of chondrogenesis of WJ-MSCs on the PLGA scaffold the expression of the key markers collagen type II and aggrecan was increased. Conclusions The observed changes in transcriptional activity of cartilaginous genes suggest that the PLGA scaffolds may be applied for WJ-MSC differentiation. This primary study suggests that chondrogenic capacity of WJ-MSCs cultured on the PLGA scaffolds can be useful for cell therapy of cartilage.